Numerical investigation on ejector as an expansion device using R290 in residential air conditioner for various cooling capacity - Haryono, A. P. (Asian Research Publishing Network, 2016)
Typically, the residential air conditioner uses capillary tube as an expansion device. The friction between refrigerant flow and pipe wall, and also the changing of the velocity along capillary tube cause energy loss during expansion. The pressure drop from the condenser to the evaporator caused by capillary tube is considered isenthalpic process. An ejector as an expansion device can be used to recover energy loss during expansion process. Many researchers reported that the use of an ejector as an expansion device in vapor compression refrigeration cycle (VCRC) may lead to increase in the system performance. In this study, the numerical investigations were carried out on the residential air conditioners using the VCRC for various cooling capacity with R290 as working fluid. At present, the working fluid of R22 is widely used as refrigerant in residential air conditioners. Because R22 has a high global warming potential (GWP), as a result it must be phased out in the near future. Researchers recommended R290 (propane) as a substitute refrigerant for R22. As a natural refrigerant, R290 is abundant and relatively cheaper than that of R22. In addition, many studies reported that retrofit from R22 to R290 in air conditioner may result increase in coefficient of performance (COP). As a result, this study investigates the use of R290 for replacing R22 in residential air conditioner for various cooling capacity, viz. 2.5, 3.8 and 5.0 kW or the compressor capacity of 1, 1.5 and 2 HP. Three equations, i.e., conservation equations of mass, momentum and energy were applied to determine physical properties on each section of the ejector and the performances of the air conditioners. The main geometrics parameter of an ejector is area ratio (AR), which is defined as the ratio between the cross-sectional areas of mixing chamber and motive nozzle. The results showed that the diameter of motive nozzle is constant with the increase in ambient temperature, whereas the mixing chamber diameter slightly increases with the increase in ambient temperature. Meanwhile, the area ratio of ejector decreases with the increase in compressor capacity. In addition, the COP improvements of air conditioners are 4.94, 12.24 and 20.28% for ambient temperature of 30, 35 and 40 °C, respectively.